Basics of successful business planning - Osgood, William R. (New York : AMACOM, 1980)
Basics of Successful Business Planning is written for people who want to go into business for themselves and aren't sure of what to do, or worse, are already in business and simply do not understand what they are doing or should be doing, There are many books and other publications available that purport to reveal the mysterious secret of success in business. This book too promises to reveal the secret of success in business, but at the same time it demystifies it. In fact, you will see that business planning is a very straightforward systematic process.
1. Why Planning? -- 2. Planning Defined -- 3. A Basic Business Planning Framework -- 4. Elements of the Planning Process -- 5. The Mechanics of Planning -- 6. Description of the Business -- 7. Financial Data -- 8. The Mechanics of Finances -- 9. The Mechanics of Management.
Includes index.
Keywords: SMALL BUSINESS -- MANAGEMENT